2015
DOI: 10.1016/j.jcol.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic difficulty in Peutz–Jeghers syndrome

Abstract: A case of diagnostic difficulty facing the patient with colonic polyposis secondary to Peutz–Jeghers syndrome, but without family history and pathognomonic clinical features of the disease, is illustrated. The exams, including biopsy, led to diagnostic uncertainty and the definitive diagnosis was characterized in therapeutic of exception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…3 It is estimated that approximately only 25% of patients with PJS have negative family history. 4 Study patient also had negative family history. In patients with PJS, polypectomy is recommended if the polyp size is more than 1cm in order to prevent the occurrence of intestinal obstruction.…”
Section: Discussionmentioning
confidence: 95%
“…3 It is estimated that approximately only 25% of patients with PJS have negative family history. 4 Study patient also had negative family history. In patients with PJS, polypectomy is recommended if the polyp size is more than 1cm in order to prevent the occurrence of intestinal obstruction.…”
Section: Discussionmentioning
confidence: 95%
“…The syndrome appears equally in males and females and is found in all racial groups [ 6 ]. The clinical manifestation of PJS is characterized by asymptomatic periods interspersed with complications, such as abdominal pain, intussusception often leading to intestinal obstruction, polyp extrusion through the rectum, and bleeding, which is often occult [ 7 , 10 , 11 ]. Small bowel obstruction is the presenting complaint in half of the cases, and relaparotomy due to polyp-induced complications occurs commonly and might do so at quite short intervals [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis involving six studies and 210 patients showed a cumulative risk of 93% from 15 to 64 years for all types of malignancies. Thus, the relative risk of an individual with SPJ to present neoplasia in any region, compared with the general population, is up to 15 times higher [ 11 , 12 ]. The most frequent neoplasm in patients with PJS is the colonic tumor (57%), followed by breast (45%), pancreas (36%), stomach (29%), ovary (21%), small intestine (13%), and uterus (10%) tumors [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, data from the literature revealed also cases where no mucocutaneous changes were noticed, as in the case of a 44-year-old male patients reported by Loureiro et al, resulting in an increased difficulty of establishing the diagnosis of PJS. [13]…”
Section: Discussionmentioning
confidence: 99%